Working Memory and the Enactment Effect in Early Alzheimer's Disease. (28th January 2014) - Charlesworth, Lara A.; Allen, Richard J.; Morson, Suzannah; Burn, Wendy K.; Souchay, Celine
Abstract : This study examines the enactment effect in early Alzheimer's disease using a novel working memory task. Free recall of action-object instruction sequences was measured in individuals with Alzheimer's disease( n = 14 ) and older adult controls( n = 15 ) . Instruction sequences were read out loud by the experimenter (verbal-only task) or read by the experimenter and performed by the participants (subject-performed task). In both groups and for all sequence lengths, recall was superior in the subject-performed condition than the verbal-only condition. Individuals with Alzheimer's disease showed a deficit in free recall of recently learned instruction sequences relative to older adult controls, yet both groups show a significant benefit from performing actions themselves at encoding. The subject-performed task shows promise as a tool to improve working memory in early Alzheimer's disease.